Effect of Profitability, Firm Size and Liquidity on Firm Value With Capital Structure as Intervening Variable - Pertiwi, Setiawati; Rahmawati, Ika Yustina; Darmawan, Akhmad; Innayah, Maulida Nurul (Media Ekonomi, 2023)
The purpose of this research was to examine the role of capital structure in mediating the effect of profitability, firm size, and liquidity towards firm value. The object of this research in manufacturing companies which is listed in the Indonesia Stock Exchange. The data used are secondary data from the 2017-2020 annual financial statements. The collection technique in this research was purposive sampling while the data analysis techniques used in this research is multiple regression analysis and hypothesis testing. The analysis results showed that the profitability has a negative effect toward capital structure, firm size has a positive effect toward capital structure, while liquidity has a negative effect toward capital structure. Meanwhile the profitability has a positive effect toward firm value, firm size has a negative effect toward firm value, while liquidity has no effect toward firm value. Capital structure is able to mediate the effect of profitability, firm size and liquidity towards firm value.